Soluble and cleaved forms of the urokinase-receptor: degradation products or active molecules? - Montuori, Nunzia; Visconte, Valeria; Rossi, Guido; Ragno, Pia (Thrombosis and Haemostasis, 2005)
The urokinase-mediated plasminogen activation (PA) system is involved in many physiological and pathological events that include cell migration and tissue remodelling, such as embryogenesis, ovulation, inflammation, wound healing, angiogenesis, and tumor invasion and metastasis. The urokinase receptor (uPAR) is a key molecule of this system and can bind extracellular and cell membrane molecules such as urokinase (uPA), vitronectin (VN), integrins and chemotaxis receptors. These multiple interactions can be modulated by the shedding or the cleavage of the cell membrane receptor. Indeed, cleaved forms of uPAR, lacking the N-terminal D1 domain, have been detected on the surface of cells and in tissues, while soluble forms have been found in biological fluids. Cleaved and soluble forms could represent the intermediary products of the uPAR metabolism or active molecules with precise and distinct functional roles. Here, we review the data concerning the in vitro and in vivo identification of these uPAR forms, their origin and functions, and the role that uPAR shedding and cleavage could play in biological processes.
Keywords: Urokinase-receptor; uPAR; suPAR; cleaved uPAR; cancer